KOMODIFIKASI BUDAYA: RELASI FAKTA, TEGANGAN DAN NEGOSIASI PERGESERAN KOMPONEN BUDAYA DALAM KARYA-KARYA SASTRAWAN MUDA SASTRA BALI MODERN - I Gede Gita Purnama Arsa Putra; Ida Bagus Gede Paramita (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Cultural commodification that occurs in the components of Balinese culture is one of the attractions of young writers of modern Balinese Literature. The phenomenon of the commodification of culture then becomes one of the choices of idea for their work and becomes their response as part of the social community. The massive commodification of Balinese culture produces tension and negotiation among the individuals within the Balinese community. Through modern Balinese literary authors, socio-cultural reflections in the community as the effect of cultural commodification can be read carefully.